Position Paper: Software Modeling Education - Seidl, Martina; Clarke, Peter (Electronic Communications of the EASST, 2012)
Model-driven engineering (MDE) is a promising paradigm to deal with the ever increasing complexity of modern software systems. Its powerful abstraction mechanisms allow practitioners to focus on the essential development challenges, thereby hiding the irrelevant aspects of the system under development. Within the last few years, noticeable progress has been made in putting MDE into practice,particularly in those areas where the activity of programming is substituted by modeling. The recent availability of matured concepts and stable tools has resulted in MDE becoming more applicable in software engineering projects. Nevertheless, the availability of the best technology is worthless, if it is not accepted and used by practitioners in the field. To alleviate this problem there is a need for extensive training both in academia and industry to fully exploit the power of MDE. In this paper, we discuss the efforts being undertaken in the educational communities to promote the application of modeling and MDE technologies and discuss several challenges which still need to be addressed.